2018
DOI: 10.5296/ajfa.v10i2.13749
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Corporate Risk-taking

Abstract: This paper studies the influence of religiosity on corporate risk-taking. The study uses unique micro-level data on religious devotion and distinguishes between manager religiosity, firm intrinsic religiosity, firm extrinsic religiosity, and social capital. Analysis shows that manager religiosity is associated with lower risk-taking. Firm intrinsic religiosity however, moderates this association. Further analysis shows that managers of Islamic firms are more likely to make risky decisions as compared to manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
1
6
2
Order By: Relevance
“…This study found evidence that age had no effect on risk-taking. The results of this study do not support research conducted by [5], [7]. Research [5] shows that age has a negative influence on investment risk-taking.…”
Section: B) Effect Of Age Variable On Investment Risk-takingcontrasting
confidence: 97%
See 4 more Smart Citations
“…This study found evidence that age had no effect on risk-taking. The results of this study do not support research conducted by [5], [7]. Research [5] shows that age has a negative influence on investment risk-taking.…”
Section: B) Effect Of Age Variable On Investment Risk-takingcontrasting
confidence: 97%
“…The results showed that companies headquartered in areas with a high level of religiosity would have a risk of low share price collisions. [5] examined the relationship between religion and corporate risk-taking. The researcher uses micro-level data that distinguishes between managerial religiosity, firm intrinsic religiosity, corporate extrinsic religiosity, and social capital.…”
Section: Literature Review 21 Religiosity and Investment Risk Takingmentioning
confidence: 99%
See 3 more Smart Citations